Los usos estratégicos de la observación electoral. El caso de la Alianza Cívica en México (1994-2012) - Navarro Rodríguez, Tania (El Colegio de México A.C., 2017)
Debates have raged in Mexico on electoral fraud since the late 1980s. This led to the foundation of an organization aimed at protecting political and electoral rights: the Alianza Cívica. Intended since its creation to observe elections, the organization has implemented activities to better monitor the practices of those in power. Based on extensive social and historical research, this paper sets out how the organization’s range of activities was established and expanded. Introducing the sociology of law and texts on international relations, it also reveals, on the one hand, the current tensions between Alianza Cívica and diverse international actors that promote “free and fair” elections and, on the other, how recourse to the law enables actors on the margins of the political contest to raise questions about delicate matters such as trust in public institutions and political authority.